THUG LIFE: Drill music as a periscope into urban violence in the consumer age. (3rd March 2020) - Lynes, Adam; Kelly, Craig; Kelly, Emma
Abstract: This paper seeks to develop an understanding of interpersonal violence within an urban landscape. An increase in violent crime has garnered intense media attention with drill—an emerging subgenre of hip hop—being sighted by media outlets as a causal factor for the rise in gang-related violence. Within this perspective, the Metropolitan Police took action, which affirmed this narrative. This paper seeks to refute such simplistic discussions of interpersonal violence whilst recognizing the opportunity such notions pose for academics to utilize knowledge of subcultures to explore possible insights into the wider understanding of violence and capitalism.